2017
DOI: 10.1084/jem.20161867
|View full text |Cite
|
Sign up to set email alerts
|

IKKα controls ATG16L1 degradation to prevent ER stress during inflammation

Abstract: Decreased ATG16L1 stabilization is associated with increased susceptibility to develop inflammatory bowel diseases. Diamanti et al. identify IKKα as a central upstream kinase of ATG16L1, providing evidence that ATG16L1 stabilization is controlled by phosphorylation downstream of TNF and NOD activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 60 publications
2
74
0
1
Order By: Relevance
“…Contrarily, prolonged ER stress and/or autophagy would be detrimental and potentially of pathophysiological significance (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, prolonged ER stress and/or autophagy would be detrimental and potentially of pathophysiological significance (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to address how the mitochondria-to-ATF6/DAPK1/autophagy interaction is impacted by other molecules that control epithelialmicrobe interaction (e.g. NOD proteins, NFkb and the inflammasome (38,46,47)). For instance, cells devoid of NOD2 are more sensitive to DNP-induced barrier defects (48) and reduced epithelia autophagy due to knockout of the amino-acid sensor GCN2 (a starvation model analogous to DNP exposure) was linked to ROS generation, inflammasome activation and intestinal inflammation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Calpain-mediated cleavage of ATG5 and beclin 1 has also been shown to be increased in patients with colitis, suggesting that autophagy protein stability in the intestine may underlie the inflammation that contributes to IBD 111 . Finally, recent studies have identified a role for IKKα in the phosphorylation and stabilization of ATG16L1 to prevent caspase-dependent cleavage in response to extracellular stimuli, further highlighting the important of ATG16L1 stabilization during inflammation 112 .…”
Section: Autophagy and Inflammatory Bowel Diseasementioning
confidence: 95%
“…Indeed, in patients with ATG16L1 T300A and in Atg16l1 ΔIEC mice, IRE1α accumulates in Paneth cells (11). In a related pathway, NOD2 signaling triggers IκB kinase α (IKKα) activation, which directly phosphorylates and stabilizes ATG16L1 (12). In the absence of IKKα, removal of IRE1α clusters is disrupted (12).…”
mentioning
confidence: 99%
“…In a related pathway, NOD2 signaling triggers IκB kinase α (IKKα) activation, which directly phosphorylates and stabilizes ATG16L1 (12). In the absence of IKKα, removal of IRE1α clusters is disrupted (12). With increasing age, Atg16l1 ΔIEC mice develop Crohn’s disease–like ileitis (11) similar to the ileitis in young Atg16l1;Xbp1 ΔIEC mice (1), and both types of ileitis are driven by accumulation and hyperactivation of IRE1α (1, 11).…”
mentioning
confidence: 99%